Dirty Pleasures: The Ethics of the Representation of Sexual Violence - Rose, David (Philosophical journal of conflict and violence, 2018)
The aim of this paper is to assert that any moral critique or political censorship of sexually violent imagery cannot be justified with reference to participants nor matters of taste. Rather, the present paper seeks to distinguish objectification and alienation and apply this distinction to the issue of the representation of sexual violence. Alienation is the morally problematic category because systems of domination and control determine the expressions and consumption of desires, but this means that the violence in such material may well be a red herring.